Enhancing Character Education and Islamic Values of Aswaja for IPNU IPPNU Students - Thohir, Muhyidin; Setiawan, Agus; Jannah, Asriatul; Alawiyah, Ika Trisnawati; Dea, Leli Fertiliana; Dewi, Yuli Ani Setyo (CV. BImbingan Belajar Assyfa, 2024)
In recent years, the rise of concerning behaviors such as the dissemination of pornographic content, student demonstrations turning violent, inter-student conflicts, exam cheating, and drug involvement have highlighted a critical deficiency in student character and values. Character education rooted in the Islamic values ​​of Ahlussunah Waljama'ah (Aswaja) is essential to address these issues. This service aims to enhance and fortify the character and Aswaja values ​​among students, particularly those in the IPNU-IPPNU Metro City organization. Utilizing the Asset-Based Community Development (ABCD) approach, the program follows a structured path of discovery, dream, design, define, and destiny phases. The initiative has yielded significant outcomes, including heightened understanding and reinforcement of Aswaja values, practical application of these values ​​in students' daily lives, and active participation from parents and the community. These results underscore the program's effectiveness in fostering well-rounded, value-driven individuals.